2010
DOI: 10.1002/ana.22055
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis, dementia, and Alzheimer disease in the Baltimore Longitudinal Study of aging cohort

Abstract: Objective-Although it is now accepted that asymptomatic cerebral infarcts are an important cause of dementia in the elderly, the relationship between atherosclerosis per se and dementia is controversial. Specifically, it is unclear whether atherosclerosis can cause the neuritic plaques and neurofibrillary tangles that define Alzheimer neuropathology and whether atherosclerosis, a potentially reversible risk factor, can influence cognition independent of brain infarcts.Methods-We examined the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(152 citation statements)
references
References 54 publications
8
136
2
6
Order By: Relevance
“…51 The BLSA data also raise the possibility that large diameter vessel intracranial atherosclerosis has a local effect upon the brain to produce dementia that is independent of the presence of cerebral infarction, systemic atherosclerosis (carotid disease) and AD pathology. 18 According to these authors, these data support the view of 'an association between atherosclerosis and cognition that is independent of cerebral infarction'. An explanation for this would be a common mechanism that produces both intracranial atherosclerosis and neurodegeneration (dementia), such as oxidative stress, disruption of the BBB, or dysfunction of communication between local blood flow and neuron metabolism (neurovascular unit).…”
Section: A Note Of Caution Regarding the Significance Of Subcorticalmentioning
confidence: 62%
See 2 more Smart Citations
“…51 The BLSA data also raise the possibility that large diameter vessel intracranial atherosclerosis has a local effect upon the brain to produce dementia that is independent of the presence of cerebral infarction, systemic atherosclerosis (carotid disease) and AD pathology. 18 According to these authors, these data support the view of 'an association between atherosclerosis and cognition that is independent of cerebral infarction'. An explanation for this would be a common mechanism that produces both intracranial atherosclerosis and neurodegeneration (dementia), such as oxidative stress, disruption of the BBB, or dysfunction of communication between local blood flow and neuron metabolism (neurovascular unit).…”
Section: A Note Of Caution Regarding the Significance Of Subcorticalmentioning
confidence: 62%
“…The prospective Baltimore Longitudinal Study of Aging (BLSA) examined 179 brains of 579 participants 18,23 and showed that the number of macroscopic hemispheric infarcts, either obvious or clinically silent, contributed to 35% of the dementia cases in the study. It was the presence of a cerebral infarct and not any associated risk factors, such as coronary artery disease and hypertension, that determined the risk of dementia.…”
Section: A Note Of Caution Regarding the Significance Of Subcorticalmentioning
confidence: 99%
See 1 more Smart Citation
“…High CRP facilitates the formation of foam cells in the process of atherogenesis [25] and also impairs endothelial function by attenuating the production of nitric oxide [35]. Both processes contribute the cognitive decline in older adults [36]. In addition, increased myo-inositol signal is a neurochemical abnormality associated with cognitive decline and Alzheimer's disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…L'étude anatomopathologique de 200 cerveaux de la Baltimore Longitudinal Study of Aging [29] montre que seule l'athérosclérose intracrânienne majore l'apparition de lésions de MA, indépendamment de la pré-sence d'infarctus cérébraux.…”
Section: Tabagismeunclassified